Smart Nutrition Kitchen : Model Pemberdayaan Keluarga Berbasis Pangan Lokal untuk Pencegahan Stunting - Etik Sulistyorini; Salsabila Amalia Putri Bumi; Fitria Hayu Palupi; Joice Merry Christy Samuel; Reinata Candra Dewi (PADMA, 2025)
Stunting remains a major nutritional problem affecting the quality of human resources in Indonesia, including in Madegondo Village, Sukoharjo. Although local food resources such as catfish, tempeh, moringa, and cassava are abundant, they have not been optimally utilized for family nutrition. The Smart Nutrition Kitchen program was designed to empower communities through nutrition education, training in local food processing, the establishment of a community nutrition kitchen, and strengthening fathers’ roles in household food security. The implementation methods included counseling, training, hands-on practice, mentoring, and continuous evaluation involving posyandu cadres, mothers, and fathers of under-five children. The results showed a significant improvement in nutrition knowledge among cadres (from 48% to 97%) and mothers (from 31% to 82%) after the intervention. In practice, 70% of mothers successfully applied innovative local food recipes, while 30% adapted them to family preferences. Fathers’ participation also increased, with 70% of families starting home food security practices through hydroponics, polybag gardening, or catfish farming. This program has proven effective in improving knowledge, skills, and family involvement in utilizing local food, while also creating economic opportunities through local food-based products. Therefore, the Smart Nutrition Kitchen has the potential to serve as a sustainable model for stunting prevention based on household food self-reliance.